2019
DOI: 10.1097/phm.0000000000001106
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Magnetic Resonance Imaging-Based Graft Maturity and Outcomes After Anterior Cruciate Ligament Reconstruction Using International Knee Documentation Committee Score

Abstract: Objective The correlation between the signal/noise quotient values of an anterior cruciate ligament graft and the International Knee Documentation Committee Subjective Knee Form 2000 scores after anterior cruciate ligament reconstruction was evaluated. Design Magnetic resonance imaging and clinical evaluation using International Knee Documentation Committee scores were used to calculate the signal intensity of the graft maturity at the 6-mo and 12-mo fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The results suggest that the greater the graft maturity, the better the surgery functional results. 37 These results corroborate those found by Biercevicz et al, 39 who correlated the graft maturity, measured by intensity and diameter at MRI, and the clinical and functional results (residual laxity and single hop-test).…”
Section: Image Criteriasupporting
confidence: 89%
See 1 more Smart Citation
“…The results suggest that the greater the graft maturity, the better the surgery functional results. 37 These results corroborate those found by Biercevicz et al, 39 who correlated the graft maturity, measured by intensity and diameter at MRI, and the clinical and functional results (residual laxity and single hop-test).…”
Section: Image Criteriasupporting
confidence: 89%
“…Li et al 37 initially did not find clinical importance in graft signal changes in magnetic resonance imaging (MRI) performed post-ACLR and did not associate the findings with graft strength/resistance, but suggest that the decrease in graft signal intensity is directly related to better scores on the International Knee Documentation Committee (IKDC), especially after 12 months of surgery. Hofbauer et al 38 compared MRI of post-ACLR knees with those of healthy knees.…”
Section: Image Criteriamentioning
confidence: 99%
“…Similar significant associations were found at 5-year follow-up in Knee injury and Osteoarthritis Outcome Score subscores. A recent study by Li et al 22 indicated that the IKDC scores 12 months after single-bundle ACLR were significantly correlated with the SNQ values of the graft measured at 6 and 12 months. They concluded that the SNQ value can predict the clinical outcomes and help decision making for return to sport.…”
Section: Discussionmentioning
confidence: 96%
“…Li et al [9] reported that MRI-based ACL graft maturity does not predict clinical and functional outcomes during the rst year after ACL reconstruction. However, Li et al [5] demonstrated that early measurement of graft maturity can predict clinical outcomes after ACL reconstruction, and the SNQ can be used for the determination of the prognosis of patients. Despite some positive ndings in graft maturation and knee function scores, further studies are needed to determine whether the SNQ value based on MRI can be used to predict knee function.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal is to restore stability and improve knee joint function as much as possible [1,2]. The Tegner, Lysholm, and International Knee Documentation Committee (IKDC) scores are important evaluation indices of knee joint function after ACL reconstruction [3][4][5]. Weiler et al [6] found that the signal/noise quotient (SNQ) based on magnetic resonance imaging (MRI) can well display the vascularization and ligamentization process of grafts and revealed that graft maturity (SNQ value) was negatively correlated with the maximum failure load, tensile strength, and stiffness of grafts [7,8].…”
Section: Introductionmentioning
confidence: 99%